Pharmaceuticals, hazard and ecotoxicity in surface and wastewater in a tropical dairy production area in Latin America - Ramírez Morales, Didier Daniel (2023)
Pharmaceuticals comprise a complex group of emerging pollutants. Despite the significant number of pharmaceuticals used in veterinary medicine, the input of these compounds into the environment due to livestock activities has been scarcely described. This work assays for the first time in Central America the occurrence of pharmaceuticals in farm wastewater in an area devoted to dairy production, and in the surrounding surface waters. Among 69 monitored pharmaceuticals, a total of eight compounds were detected in wastewater samples collected from seven dairy farms after three sampling campaigns. Six pharmaceuticals were considered either of high (albendazole, lovastatin and caffeine) or intermediate estimated hazard (ciprofloxacin, acetaminophen and ketoprofen) based on the HQ approach, while 26% of the samples were considered of high estimated hazard according to the cumulative ∑HQ approach. Similarly, when ecotoxicological tests were applied, all the samples showed some level of toxicity towards Daphnia magna, and most samples towards Vibrio fischeri and Lactuca sativa. Fourteen pharmaceuticals were detected in surface water samples collected in the surroundings of the dairy production farms, including rural and urban areas. Seven out of these compounds showed high estimated risk (risperidone, diphenhydramine, trimethoprim, fluoxetine, ofloxacin, caffeine and ibuprofen), while three (gemfibrozil, ciprofloxacin and cephalexin) exhibited intermediate estimated risk. In a similar worrisome way, 27% of these samples were estimated to pose high environmental risk according to the pharmaceutical content. Despite being nontoxic for D. magna or V. fischeri, frequent inhibition (>20%) of GI in L. sativa was determined in 34% of surface water samples; such findings raise concern on the apparent inceptive environmental pollution and risk within the area. According to the pharmaceutical content patterns in both kinds of studied matrices, no clear evidence of significant contamination in surface water due to livestock activities could be retrieved, suggesting a main role of urban influence.